2023
DOI: 10.1186/s12884-023-05448-1
|View full text |Cite
|
Sign up to set email alerts
|

FtMt reduces oxidative stress-induced trophoblast cell dysfunction via the HIF-1α/VEGF signaling pathway

Abstract: Background Preeclampsia (PE) is a complication of pregnancy that causes long-term adverse outcomes for the mother and fetus and may even lead to death. Oxidative stress caused by the imbalance of oxidants and antioxidants in the placenta has been considered as one of the key mechanisms of preeclampsia (together with inflammation, etc.), in which the placental mitochondria play an important role. The expression of hypoxia-inducible factor-1 (HIF-1α) and vascular endothelial growth factor (VEGF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…It has been reported that mitochondria are the main sites of ROS production and mitochondrial membrane integrity is sensitive to the cellular ROS levels ( 41 ). In the present study, H/R stimulation led to suppressed proliferation, migration, invasion and elevated ROS and JC-1 monomer levels of HTR-8/SVneo cells, suggesting the damage caused by trophoblast cell dysfunction and induction of oxidative stress, which were consistent with the results of previous studies ( 17 , 42 , 43 ). At present, HSPB8 has been confirmed to be highly expressed in various human tumors and HSPB8 overexpression has been demonstrated to facilitate the proliferation, migration and invasion of these cancer cells, such as prostate cancer, gastric cancer and lung adenocarcinoma ( 44-46 ).…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that mitochondria are the main sites of ROS production and mitochondrial membrane integrity is sensitive to the cellular ROS levels ( 41 ). In the present study, H/R stimulation led to suppressed proliferation, migration, invasion and elevated ROS and JC-1 monomer levels of HTR-8/SVneo cells, suggesting the damage caused by trophoblast cell dysfunction and induction of oxidative stress, which were consistent with the results of previous studies ( 17 , 42 , 43 ). At present, HSPB8 has been confirmed to be highly expressed in various human tumors and HSPB8 overexpression has been demonstrated to facilitate the proliferation, migration and invasion of these cancer cells, such as prostate cancer, gastric cancer and lung adenocarcinoma ( 44-46 ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the hypoxic environment within the placenta creates optimal conditions for trophoblast invasion and placenta formation, while changes in oxygen partial pressure adversely affect the proliferation and invasive capacity of trophoblasts [ 24 ]. A study [ 25 ] has shown significant changes in the expression levels of Vascular Endothelial Growth Factor (VEGF) and Hypoxia-Inducible Transcription Factor 1- α (HIF-1 α ) in the chorionic tissues of patients with early RSA. STW, by decreasing the expression level of HIF-1 α mRNA and protein and simultaneously promoting the expression of VEGF and its receptor mRNA and protein, enhances the proliferation and reinforces functions of placental trophoblast cells.…”
Section: Principal Pharmacological Effects Of Stw In the Regulation O...mentioning
confidence: 99%
“…It showed that the protective effect of 4-PBA on hypoxia-induced trophoblast cells was linked to autophagy inhibition and PERK/ATF-4/CHOP pathway downregulation. Some studies have suggested that placental hypoxia is a significant pathological change in PE(Xu et al, 2023). The placental trophoblast cells, which are the main cells in the placenta, function in invasion and vascular recast and maintain the normal development of the placenta(Zhang et al, 2020).…”
mentioning
confidence: 99%